2019
DOI: 10.1111/ejh.13203
|View full text |Cite
|
Sign up to set email alerts
|

Haematological malignancy: Are we measuring what is important to patients? A systematic review of quality‐of‐life instruments

Abstract: The wide range of health‐related quality‐of‐life (HRQoL) instruments used in haematology makes it challenging for haematologists and other care team members in practice to select, use and understand the scoring system and finally interpret the results. The main objectives of this study were to: (a) provide a comprehensive list of quality‐of‐life issues important to patients suffering from haematological malignancies, identified through the literature; (b) provide a list of health‐related quality‐of‐life (HRQoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 112 publications
(233 reference statements)
0
30
0
Order By: Relevance
“…Several studies have previously reported that HM has a high impact on patients' HRQoL (Persson et al, 2001;Holzner et al, 2004;Santos et al, 2006;Mols et al, 2007;Shanafelt et al, 2007;Strasser-Weippl and Ludwig, 2008;Johnsen et al, 2009). A recent systematic review reported that there are 30 HRQoL instruments currently used in hematology and none of these instruments captures all the issues important to these patients (Goswami et al, 2019). Furthermore, this review also reports that a barrier to using patient-reported outcomes (PRO) in clinical practice is the diversity of such instruments.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies have previously reported that HM has a high impact on patients' HRQoL (Persson et al, 2001;Holzner et al, 2004;Santos et al, 2006;Mols et al, 2007;Shanafelt et al, 2007;Strasser-Weippl and Ludwig, 2008;Johnsen et al, 2009). A recent systematic review reported that there are 30 HRQoL instruments currently used in hematology and none of these instruments captures all the issues important to these patients (Goswami et al, 2019). Furthermore, this review also reports that a barrier to using patient-reported outcomes (PRO) in clinical practice is the diversity of such instruments.…”
Section: Introductionmentioning
confidence: 93%
“…follicular lymphoma patients (Osborne et al, 2015;Davies et al, 2017), and therefore cannot be applied to other HM. Among the identified 30 HRQoL instruments, only partial evidence on the content validity was identified for EORTC QLQ-MY24, FACT-Leu, EORTC Leu, FACT-Lym, QoL-E (Goswami et al, 2019). Up to 18% of the patients resported missing items for EORTC QLQ-MY24 (Goswami et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These are also the most frequently used in hematological research. 17,18 Still, intervention studies are sparse, and the use of PRO to improve treatment of hematological malignancies has not been well established. [19][20][21][22][23] In 2011-2012, the Blood Cancer Registry 24 decided to start a pilot project using PRO in the acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) registries.…”
Section: Introductionmentioning
confidence: 99%
“…The framework builds on the assumption that the patient-doctor relationship is crucial in providing holistic, patient-centred care and alleviating the symptom burden caused by the disease or treatment. PROMs can help identify symptom burden and inform the decision-making process, leading to initiation of supportive care [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Adaption of PROMs has also been linked to measurement uncertainties, including content validity (content relevance and content coverage) and the psychometric properties of the PROM(s) [17,18]; inadequate measurement properties could potentially lead to clinicians using invalid outcomes when consulting with patients, which again could potentially be harmful and detrimental to the patient-doctor relationship. Important knowledge gaps remain regarding the complexity of PROMs usage and how to adapt them across different settings for routine clinical care [3,4]. Despite an extensive volume of literature on the use of PROMs for routine clinical care, it is difficult to reach firm conclusions due to the broad variety of interventions within settingspecific studies [4,19,20].…”
Section: Introductionmentioning
confidence: 99%